Decision-making conversations for life-sustaining treatment with seriously ill patients using a Danish version of the US POLST: a qualitative study of patient and physician experiences - Lone Doris Tuesen; Anne Sophie Ågård; Hans-Henrik Bülow; Erik K. Fromme; Hanne Irene Jensen (Taylor & Francis Group, 2022)
Objective To explore patients' and physicians' perspectives on a decision-making conversation for life-sustaining treatment, based on the Danish model of the American Physician Orders for Life Sustaining Treatment (POLST) form. Design Semi-structured interviews following a conversation about preferences for life-sustaining treatment. Setting Danish hospitals, nursing homes, and general practitioners' clinics. Subjects Patients and physicians. Main outcome measures Qualitative analyses of interview data. Findings After participating in a conversation about life-sustaining treatment using the Danish POLST form, a total of six patients and five physicians representing different settings and age groups participated in an interview about their experience of the process. Within the main research questions, six subthemes were identified: Timing, relatives are key persons, clarifying treatment preferences, documentation across settings, strengthening patient autonomy, and structure influences conversations. Most patients and physicians found having a conversation about levels of life-sustaining treatment valuable but also complicated due to the different levels of knowledge and attending to individual patient needs and medical necessities. Relatives were considered as key persons to ensure the understanding of the treatment trajectory and the ability to advocate for the patient in case of a medical crisis. The majority of participants found that the conversation strengthened patient autonomy. Conclusion Patients and physicians found having a conversation about levels of life-sustaining treatment valuable, especially for strengthening patient autonomy. Relatives were considered key persons. The timing of the conversation and securing sufficient knowledge for shared decision-making were the main perceived challenges.KEY POINTS Conversations about preferences for life-sustaining treatment are important, but not performed systematically. When planning a conversation about preferences for life-sustaining treatment, the timing of the conversation and the inclusion of relatives are key elements. Decision-making conversations can help patients feel in charge and less alone, and make it easier for health professionals to provide goal-concordant care. Using a model like the Danish POLST form may help to initiate, conduct and structure conversations about preferences for life-sustaining treatment.